Motor Imagery and Action Observation as Appropriate Strategies for Home-Based Rehabilitation: A Mini-Review Focusing on Improving Physical Function in Orthopedic Patients - Paravlic, Armin H. (Frontiers in Psychology, 2022)
Dynamic stability of the knee and weakness of the extensor muscles are considered to be the most important functional limitations after anterior cruciate ligament injury, probably due to changes at the central (cortical and corticospinal) level of motor control rather than at the peripheral level. Despite general technological advances, fewer contraindicative surgical procedures, and extensive postoperative rehabilitation, up to 65% of patients fail to return to their preinjury level of sports, and only half were able to return to competitive sport. Later, it becomes clear that current rehabilitation after knee surgery is not sufficient to address the functional limitations after ACL reconstruction even years after surgery. Therefore, new therapeutic tools targeting the central neural system, i.e., the higher centers of motor control, should be investigated and integrated into current rehabilitation practice. To improve motor performance when overt movement cannot be fully performed (e.g., due to pain, impaired motor control, and/or joint immobilization), several techniques have been developed to increase physical and mental activation without the need to perform overt movements. Among the most popular cognitive techniques used to increase physical performance are motor imagery and action observation practices. This review, which examines the available evidence, presents the underlying mechanisms of the efficacy of cognitive interventions and provides guidelines for their use at home.